Strategies for Improved Intra-arterial Treatments Targeting Brain Tumors: a Systematic Review - Huang, Rui; Boltze, Johannes; Li, Shen (Frontiers in Oncology, 2020)
Conventional treatments for brain tumors relying on surgery, radiation and systemic chemotherapy are often associated with high recurrence and poor prognosis. Since a few decades, intra-arterial administration of anti-cancer drugs is considered a suitable alternative drug delivery route to intravenous and oral administration. Intra-arterial administration is believed to offer increasing drug responses by primary and metastatic brain tumors, and to be associated with better median overall survival. By directly injecting therapeutic agents into carotid or vertebral artery, intra-arterial administration rapidly increases intra-tumoral drug concentration but lowers systemic exposure. However, unexpected vascular or neural toxicity has questioned the therapeutic safety of intra-arterial drug administration, and limits its widespread clinical application. Therefore, improving targeting and accuracy of intra-arterial administration has become a major research focus. This systematic review categorizes strategies for optimizing intra-arterial administration into five categories, (i) transient blood-brain barrier (BBB)/ blood-tumor barrier (BTB) disruption, (ii) regional cerebral hypoperfusion for peritumoral hemodynamic changes, (iii) superselective endovascular intervention, (iv) high-resolution imaging techniques, and (v) others such as cell and gene therapy. We summarize and discuss both preclinical and clinical research, focusing on advantages and disadvantages of different treatment strategies for a variety of cerebral tumor types.